Upaya Italia Membangun Destination Branding Melalui Strategi Wine Tourism Tahun 2017 – 2021 - Puspitasari, Putri Ayu; Priadarsini, Ni Wayan Rainy; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
In the context of International Relations, tourism is one of the drivers of a country's economy, social and cultural aspects, and even its environment. For a country, destination branding is a good strategy to make it attractive to tourists. Generally, destination branding is used by a country to make it memorable, thereby enhancing its value as a tourist destination. Italy is one of the countries that prioritize the tourism sector. This is because tourism is one of Italy's largest sources of foreign exchange. Wine tourism is one of the instruments Italy uses to boost its tourism sector. Italy is known for having one of the best wine tourism experiences in the world. In its development, Italy's wine tourism strategy has promoted three components of destination branding: 1) Product (high-quality wine itself), 2) Place (functional and monumental wineries), and 3) People (wine festivals with the participation of local residents). Some unique findings in this research include the impacts generated by Italy's wine tourism strategy, such as increased tourists, an enhanced image of Italian wine production, and increased popularity of Italian culture. The important role of social movements or communities in Italy's destination branding development, such as Citta del Vino, is also highlighted, as well as the potential success of Italy's destination branding with a focus on cities (city branding), such as Tuscany.